1985
DOI: 10.1161/01.cir.71.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to the stress of tachycardia in patients with coronary artery disease: insight into the mechanism of the warm-up phenomenon.

Abstract: Adaptation to exercise or the "warm up phenomenon" has been observed in some patients with angina pectoris. To investigate adaptation, eleven patients with exertional angina pectoris and angiographic evidence of coronary artery disease underwent two identical bouts of sequential tachycardia stress separated by a brief recovery period. Manifestations of ischemia were less during the second stress, as evidenced by a reduction in the severity of angina pectoris, less ST segment depression, and improved lactate ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 17 publications
(5 reference statements)
4
36
0
Order By: Relevance
“…In placebo-treated patients, the blood glucose level before the exercise test (96 10 mg . 100 ml 1 ) was similar to that found in glibenclamide-treated patients (P=ns) ( Table 1). …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In placebo-treated patients, the blood glucose level before the exercise test (96 10 mg . 100 ml 1 ) was similar to that found in glibenclamide-treated patients (P=ns) ( Table 1). …”
Section: Resultssupporting
confidence: 85%
“…The warm-up phenomenon usually refers to increased tolerance to myocardial ischaemia during the second of two sequential exercise tests [1][2][3][4][5] . Although this phenomenon was described in anginal patients more than 50 years ago [6] , its underlying mechanisms remain poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Warm-up is also unexplained by the recruitment of collateral vessels. 20 Instead, it has been suggested that warm-up is a result of attenuation of increased regional myocardial oxygen consumption (MVO 2 ), possibly mediated by adenosine A 1 receptor activation, a signaling system known to improve tolerance to ischemia.…”
Section: Coronary Blood Flow and Oxygen Consumptionmentioning
confidence: 99%
“…110 Regional myocardial oxygen consumption was lower during the second test than the first, and flow through the cardiac vein did not differ between tests. Williams et al 111 induced angina by pacing-induced tachycardia at the time of catheterization. Two identical periods of pacing were separated by a 5-to 15-minute rest phase.…”
Section: Preconditioning In Patientsmentioning
confidence: 99%